Kebijakan Sistem Pemidanaan dalam Upaya Perlindungan Hukum terhadap Anak yang Berkonflik dengan Hukum Menurut Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak - Christianingrum Ari Pramono Putri, Eko Soponyono*, Pujiyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Child is the next generation of the nation that still have limitations in thought, action, and assess which ones are good or bad that mandatory protection in various aspects, by anyone, including the state. To face the child who did the offence needs to consider the position of the child as well as all the characteristics. Legally, Indonesia has granted protection to the child through various regulations, one of which the latest is Act No. 11 in 2012 about the Child Criminal Justice System. Although the new rules is more protecting child than the previous one, but the protection of children in Indonesia is still weak and leaving the character of sanctions that has sort of retaliation to the child.